Radiographic form of periodontal tissue damage: Bentuk kerusakan struktur jaringan periodontal secara radiografis - Barunawaty Yunus; Hatimurni (Makassar Dental Journal PDGI Makassar, 2022)
Radiographic examination is one of the important supports in the periodontal field. Periodontal radiographs were used to as-sess the widening of the periodontalligament space, continuity of the lamina dura, height and shape of the alveolar crest, bone loss, interdental crater, and furcation defects. The shape of thedestruction of the periodontal tissue structure radiographically can give a different picture depending on the severity of periodontal disease, the radiographic technique used, or anatomical variations that resemble the disease.